2015
DOI: 10.14573/altex.1411011
|View full text |Cite
|
Sign up to set email alerts
|

Integrated testing strategies (ITS) for safety assessment

Abstract: SummaryIntegrated testing strategies (ITS), as opposed to a single definitive test or fixed batteries of tests, are expected to efficiently combine different information sources in a quantifiable fashion to satisfy an information need, in this case for regulatory safety assessments. With increasing awareness of the limitations of each individual tool and the development of highly targeted tests and predictions, the need for combining pieces of evidence increases. The discussions that took place during this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
134
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 55 publications
1
134
0
Order By: Relevance
“…During the past decade, a lot of attention has been dedicated to developing non-animal testing methods and testing strategies for the toxicological endpoint skin sensitisation (Jaworska and Hoffmann, 2010;Jaworska et al, 2011;Hartung et al, 2013;Rovida et al, 2015;Jaworska, 2016). Skin sensitisation is the toxicological endpoint assessing a substance's ability to cause allergic contact dermatitis (ACD) (UNECE, 2011).…”
Section: Addressing the Development Of Efficient Toxicity Testing Strmentioning
confidence: 99%
See 4 more Smart Citations
“…During the past decade, a lot of attention has been dedicated to developing non-animal testing methods and testing strategies for the toxicological endpoint skin sensitisation (Jaworska and Hoffmann, 2010;Jaworska et al, 2011;Hartung et al, 2013;Rovida et al, 2015;Jaworska, 2016). Skin sensitisation is the toxicological endpoint assessing a substance's ability to cause allergic contact dermatitis (ACD) (UNECE, 2011).…”
Section: Addressing the Development Of Efficient Toxicity Testing Strmentioning
confidence: 99%
“…Since non-animal testing methods are not considered suitable to provide sufficient information to draw conclusions upon the skin sensitisation potential of chemicals (Mehling et al, 2012;Reisinger et al, 2015), a solution suggested is to integrate information from different sources and testing methods by using hypothesis-based approaches such as Bayesian networks (Jaworska and Hoffmann, 2010;Jaworska et al, 2011;Hartung et al, 2013;Jaworska et al, 2013;Jaworska, 2016) or deterministic ITS approaches (Bauch et al, 2012;Urbisch et al, 2015a). For the development of integrated strategies assessing skin sensitisation potential and potency (Jaworska, 2016) different sets of criteria have been proposed including transparency, coherency, ambiguity, or cost effectiveness (Hartung et al, 2013;Rovida et al, 2015) which are applicable also for other toxicological endpoints . It has also been suggested that the combination of individual non-animal testing methods into batteries or sequential strategies should be guided by the skin sensitisation AOP (Vinken, 2013;Patlewicz et al, 2014).…”
Section: Addressing the Development Of Efficient Toxicity Testing Strmentioning
confidence: 99%
See 3 more Smart Citations